Mycobacterium tuberculosis and mycobacterium africanum in stools from children attending an immunization clinic in Ibadan, Nigeria (2009)
"BACKGROUND:Tuberculosis is a major cause of childhood morbidity and mortality in Nigeria. Diagnosis of childhood tuberculosis is a global challenge making early treatment a mirage. In this study we investigated the stools of children for the presence of mycobacteria. METHODS:Stool samples from children aged 3 days to 3 years who presented for postnatal immunization at a large university-based clinic in Nigeria, were subjected to Ziehl-Neelsen staining. Samples with acid-fast bacilli were further processed using mycobacterial culture, spoligotyping, and deletion typing. RESULTS:One hundred and ninety-two stool samples from different children were collected and processed. Thirty (15.6%) had acid-fast bacilli. Of these, eight had Mycobacterium tuberculosis and one had Mycobacterium africanum. CONCLUSIONS:Approximately 5% (9/192) of apparently well children had evidence of potentially serious tuberculosis infection. The usefulness of stool specimens for diagnosing pediatric tuberculosis warrants further investigation."